2019
DOI: 10.2147/tcrm.s216606
|View full text |Cite
|
Sign up to set email alerts
|

<p>Demographic And Clinical Characteristics Of Patients Prescribed Proprotein Convertase Subtilisin/kexin Type 9 Inhibitor Therapy And Patients Whose Current Lipid-Lowering Therapy Was Modified</p>

Abstract: Purpose: Our objective was to describe the demographic and clinical characteristics of real-world patients in the US with elevated low-density lipoprotein cholesterol (LDL-C) whose lipid-lowering therapy (LLT) ─ both proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor and non-PCSK9 inhibitor ─ was actively modified. Methods: This retrospective cohort study used linked laboratory (Prognos), pharmacy (IMS Formulary Impact Analyzer), and medical claims (IQVIA Dx/LRx or PharMetrics Plus) data. PCSK9 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This real‐world analysis describes the characteristics and LDL‐C outcomes of patients who initiated evolocumab therapy between July 1, 2015, and October 31, 2019, in US healthcare settings, including patients with a recent MI within 12 months (median 130 days) prior to starting evolocumab therapy. Overall, patient clinical characteristics were largely consistent with the recommendation that patients selected for PCSK9 inhibitor therapy are those with high levels of CV risk, 14‐16 and supports a previous real‐world study reporting that physicians were most likely to prescribe PCSK9 inhibitors to patients with elevated LDL‐C levels and additional comorbid risk factors for adverse CV events 34 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This real‐world analysis describes the characteristics and LDL‐C outcomes of patients who initiated evolocumab therapy between July 1, 2015, and October 31, 2019, in US healthcare settings, including patients with a recent MI within 12 months (median 130 days) prior to starting evolocumab therapy. Overall, patient clinical characteristics were largely consistent with the recommendation that patients selected for PCSK9 inhibitor therapy are those with high levels of CV risk, 14‐16 and supports a previous real‐world study reporting that physicians were most likely to prescribe PCSK9 inhibitors to patients with elevated LDL‐C levels and additional comorbid risk factors for adverse CV events 34 …”
Section: Discussionsupporting
confidence: 77%
“…Overall, patient clinical characteristics were largely consistent with the recommendation that patients selected for PCSK9 inhibitor therapy are those with high levels of CV risk, [14][15][16] and supports a previous real-world study reporting that physicians were most likely to prescribe PCSK9 inhibitors to patients with elevated LDL-C levels and additional comorbid risk factors for adverse CV events. 34 At baseline, LDL-C levels were markedly elevated despite the majority of patients receiving background LLT with statins and/or ezetimibe in the 12 months prior to evolocumab initiation. Of note, the 60.6% of patients treated with statins prior to evolocumab initiation in the current study is considerably higher than that reported in a recently published study where only 29.3% of patients filled a statin in the period 31-365 days prior to PCSK9 inhibitor initiation.…”
Section: Discussionmentioning
confidence: 94%
“…11 The Prognos LDL-C database has been previously used in retrospective cohort studies. [12][13][14] The aggregated IQVIA PharMetrics Plus database comprises adjudicated claims for patients across the US and is sourced directly from insurance companies, and contains data on patient's health plan claims, demographics, clinical characteristics, and occurrence of CV events.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…While several real-world studies have assessed the side effects and effectiveness (eg, LDL lowering, CV events) of PCSK9-Is, 7 , 8 , 9 , 10 all involved small numbers of patients. Furthermore, while there are multiple studies on the patterns of use, cost, accessibility, adherence, discontinuation, and overall place in therapy of PCSK9-Is in the treatment of hyperlipidemia, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 these were conducted in populations outside of the VHA. VHA is the largest integrated health care system in the United States and provides access to needed medications with nominal, or no, copayment.…”
Section: Introductionmentioning
confidence: 99%